evluate sin^6 Θ - cos^6 Θ
![{ \sin }^{6} a \: - { \cos }^{6} a { \sin }^{6} a \: - { \cos }^{6} a](https://tex.z-dn.net/?f=+%7B+%5Csin+%7D%5E%7B6%7D+a+%5C%3A++++-++%7B+%5Ccos+%7D%5E%7B6%7D+a)
plz solve this
expecting expert answer plz
Answers
Answered by
7
HELLO DEAR,
we know that;-
(a³-b³)=(a²-b²)(a⁴+b⁴+ab)----------(1)
(a⁴+b⁴)=(a²+b²)² - 2a²b²---------------(2)
sin²Θ - cos²Θ => (2sin²θ-1)--------------(3)
(sin²Θ + cos²Θ )=1---------------(1)
[ If we know that cos²θ=1−sin²θ, we can replace cos²θ with 1−sin²θ in the expression :-
(sin²Θ - cos²Θ) = sin²θ -(1−sin²θ)
(sin²Θ - cos²Θ) = (2sin²θ-1) ]
now Solve
![( \sin ^{6} \alpha - { \cos}^{2} \alpha ) = ( { \sin }^{2} \alpha)^{3} - { (\cos ^{2} \alpha ) }^{ 3} \\ = >( { \sin }^{2} \alpha - \cos^{2} \alpha )( \sin^{4} \alpha + \cos^{4} \alpha + \sin\alpha \times \cos \alpha ) ======= using...(1) \\ = > (2 { \sin }^{2} \alpha - 1)[ ({\sin }^{2} \alpha + \cos^{2} \alpha )^{2} - 2 { \sin}^{2} \alpha { \cos}^{2} \alpha +\sin\alpha \times \cos \alpha )] === using.(2)..and..(3) \\ = > (2 { \sin }^{2} \alpha - 1)[ {1} - 2 { \sin}^{2} \alpha { \cos}^{2} \alpha +\sin\alpha \times \cos \alpha )] using--(4) ( \sin ^{6} \alpha - { \cos}^{2} \alpha ) = ( { \sin }^{2} \alpha)^{3} - { (\cos ^{2} \alpha ) }^{ 3} \\ = >( { \sin }^{2} \alpha - \cos^{2} \alpha )( \sin^{4} \alpha + \cos^{4} \alpha + \sin\alpha \times \cos \alpha ) ======= using...(1) \\ = > (2 { \sin }^{2} \alpha - 1)[ ({\sin }^{2} \alpha + \cos^{2} \alpha )^{2} - 2 { \sin}^{2} \alpha { \cos}^{2} \alpha +\sin\alpha \times \cos \alpha )] === using.(2)..and..(3) \\ = > (2 { \sin }^{2} \alpha - 1)[ {1} - 2 { \sin}^{2} \alpha { \cos}^{2} \alpha +\sin\alpha \times \cos \alpha )] using--(4)](https://tex.z-dn.net/?f=%28+%5Csin+%5E%7B6%7D+%5Calpha+-+%7B+%5Ccos%7D%5E%7B2%7D+%5Calpha+%29+%3D+%28+%7B+%5Csin+%7D%5E%7B2%7D+%5Calpha%29%5E%7B3%7D+-+%7B+%28%5Ccos+%5E%7B2%7D+%5Calpha+%29+%7D%5E%7B+3%7D+%5C%5C+%3D+%26gt%3B%28+%7B+%5Csin+%7D%5E%7B2%7D+%5Calpha+-+%5Ccos%5E%7B2%7D+%5Calpha+%29%28+%5Csin%5E%7B4%7D+%5Calpha+%2B+%5Ccos%5E%7B4%7D+%5Calpha+%2B+%5Csin%5Calpha+%5Ctimes+%5Ccos+%5Calpha+%29+%3D%3D%3D%3D%3D%3D%3D+using...%281%29+%5C%5C+%3D+%26gt%3B+%282+%7B+%5Csin+%7D%5E%7B2%7D+%5Calpha+-+1%29%5B+%28%7B%5Csin+%7D%5E%7B2%7D+%5Calpha+%2B+%5Ccos%5E%7B2%7D+%5Calpha+%29%5E%7B2%7D+-+2+%7B+%5Csin%7D%5E%7B2%7D+%5Calpha+%7B+%5Ccos%7D%5E%7B2%7D+%5Calpha+%2B%5Csin%5Calpha+%5Ctimes+%5Ccos+%5Calpha+%29%5D+%3D%3D%3D+using.%282%29..and..%283%29+%5C%5C+%3D+%26gt%3B+%282+%7B+%5Csin+%7D%5E%7B2%7D+%5Calpha+-+1%29%5B+%7B1%7D+-+2+%7B+%5Csin%7D%5E%7B2%7D+%5Calpha+%7B+%5Ccos%7D%5E%7B2%7D+%5Calpha+%2B%5Csin%5Calpha+%5Ctimes+%5Ccos+%5Calpha+%29%5D+using--%284%29+)
I HOPE ITS HELP YOU DEAR,
THANKS
we know that;-
(a³-b³)=(a²-b²)(a⁴+b⁴+ab)----------(1)
(a⁴+b⁴)=(a²+b²)² - 2a²b²---------------(2)
sin²Θ - cos²Θ => (2sin²θ-1)--------------(3)
(sin²Θ + cos²Θ )=1---------------(1)
[ If we know that cos²θ=1−sin²θ, we can replace cos²θ with 1−sin²θ in the expression :-
(sin²Θ - cos²Θ) = sin²θ -(1−sin²θ)
(sin²Θ - cos²Θ) = (2sin²θ-1) ]
now Solve
I HOPE ITS HELP YOU DEAR,
THANKS
Similar questions